STRUKTUR DAN KOMPOSISI HUTAN MANGROVE DI NEGERI HATUSUA KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Rante, Queen Athalia Deborah; Sahupala, Andjela; Komul, Yulianus (MARSEGU : Jurnal Sains dan Teknologi, 2024)
The aim of this research is to determine the structure and composition of mangrove forests in Hatusua State, Kairatu District, West Seram Regency. And vegetation analysis was carried out by collecting data on the type, number, diameter and height of trees. In this research, the path method was used by carrying out a 100% inventory. The measuring plot area for the vegetation growth level of Seedlings, Saplings and Trees is 20 m x 20 m, a total of 46 plots for a total area of ​​1.84 ha. The research results show that the mangrove forests in Hatusua State can be divided into two from inundation, namely the middle zone and the distal zone, where in this mangrove forest there is no proximal zone because there are no mangroves that face the sea. The stratification of Hatusua State's mangrove forests is simpler than that of mainland natural forests. Mangrove trees in Hatusua Country can reach a tree height of 15 – 25 meters, which are dominated by Rhizophora apiculata, Heritiera littoralis, Parmentiera cereifera, and Intsia bijuga. The Hatusua State mangrove forest diversity index value of 1.37 seedlings, 2.30 saplings and 1.36 trees is categorized as medium because the value 1 <H' < 3.